Tell me How It Ends : An Essay in Forty Questions. - Luiselli, Valeria (Minneaoplis : Coffee House Press, 2017)
"Structured around the forty questions Luiselli translates and asks undocumented Latin-American children facing deportation, Tell Me How It Ends (an expansion of her 2016 Freeman's essay of the same name) humanizes these young migrants and highlights the contradiction of the idea of America as a fiction for immigrants with the reality of racism and fear--both here and back home"-- provided by publisher
boek